Frontiers of Sulfur Metabolism in Plant Growth, Development, and Stress Response - Stanislav Kopriva (Frontiers Research Topics, 2016)
Growing plants have a constitutive demand for sulfur to synthesize proteins, sulfolipids and other essential sulfur containing molecules for growth and development. The uptake and subsequent distribution of sulfate is regulated in response to demand and environmental cues. The importance of sulfate for plant growth and vigor and hence crop yield and nutritional quality for human and animal diets has been clearly recognized. The acquisition of sulfur by plants, however, has become an increasingly important concern for the agriculture due to the decreasing S-emissions from industrial sources and the consequent limitation of inputs from atmospheric deposition. Molecular characterization involving transcriptomics, proteomics and metabolomics in Arabidopsis thaliana as well as in major crops revealed that sulfate uptake, distribution and assimilation are finely regulated depending on sulfur status and demand, and that these regulatory networks are integrated with cell cycle, photosynthesis, carbohydrate metabolism, hormonal signaling, uptake and assimilation of other nutrients, etc., to enable plant growth, development, and reproduction even under different biotic and abiotic stresses. This knowledge can be used to underpin approaches to enhance plant growth and nutritional quality of major food crops around the world. Although considerable progress has been made regarding the central role of sulfur metabolism in plant growth, development and stress response, several frontiers need to be explored to reveal the mechanisms of the cross-talk between sulfur metabolism and these processes. In this research topic the knowledge on plant sulfur metabolism is reviewed and updated. Focus is put not only on molecular mechanisms of control of sulfur metabolism but also on its integration with other vital metabolic events. The topic covers 4 major areas of sulfur research: sulfate uptake, assimilation and metabolism, regulation, and role in stress response. We hope that the topic will promote interaction between researchers with different expertise and thus contribute to a more integrative approach to study sulfur metabolism in plants.